Investigation of metabolic effects of CETP gene rs289714 variation in coronary artery patients: A case-control study - Özlem Kurnaz Gömleksiz; Zeynep Karaali; Zehra Buğra; Oğuz Öztürk; Hulya Yilmaz Aydogan (KARE Publishing, 2020)
Objective: The aim of this study was to investigate the effects of the CETP gene rs289714 polymorphism on the serum lipid profile and other metabolic parameters in Turkish patients with coronary artery disease (CAD). Methods: The CETP rs289714 variant was examined in 104 patients with CAD and 77 controls using the polymerase chain reaction-restriction fragment length polymorphism method. Results: The CETP rs289714 genotype and allele distribution was not statistically different between the groups (p>0.05). The body mass index (BMI) values in men with CAD were higher in patients with the G allele compared with those carrying the AA genotype (p=0.05). Logistic regression analysis showed that the G allele in male CAD patients was a risk factor for a BMI of 27 kg/m2 (odds ratio: 0.269, 95% confidence interval: 0.075-0.966; p=0.044). The G allele in female patients was associated with lower HDL-C levels than the AA genotype (p=0.049). Conclusion: The results suggest that the CETP rs289714 polymorphism may cause risk for the development of CAD due to its effects on high-density lipoprotein cholesterol values in male patients and BMI in female patients.